PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, LEVERAGE, FREE CASH FLOW DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI - Lely Nurma Jayanti, 13.05.62.0026; Maryono, Maryono (Students Journal of Accounting and Banking, 2017)
Earnings management is the decision of the manager to choose a specific accounting policy that is deemed to be able to achieve the desired goals, whether to increase profits or reduce the level of losses reported.This study aims to examine the effect of managerial ownership, audit committee, institutional ownership, board of commissioner, leverage, free cash flow, and firm size to earnings management on manufacturing at BEI during 2013-2015 period. The population in this study are all companies engaged in the manufacturing sector listed on the Indonesia Stock Exchange (BEI) in 2013-2015. The sampling technique used purposive sampling technique that is choosing the sample with certain criteria according to the desired by the researcher, where according to the predefined criteria there are 43 samples. The analysis technique used is multiple regression. Based on the discussion of the results of this study shows that: managerial ownership, audit committee, leverage, free cash flow negatively affect earnings management. Whereas in institutional ownership variable, board of commissioner and firm size have no effect to earnings management.Keywords: Managerial Ownership, Audit Committee, Institutional Ownership, Board Of Commissioners, Leverage, Free Cash Flow, and Company Size